Theoretical Basis of Democratization and Issues towards Consolidated Democracy - Cheema, Ammara Tariq (Annals of Human and Social Sciences, 2023)
The purpose of this research is to probe democratization and democratic consolidation and this study is importance for the states, which are working to strengthen and modernize their feeble democratic setups. The democracy is a system while democratization is a process and consolidated democracy is an outcome. Democratization refers to the process of building a democracy following the collapse of a non-democratic regime. The democratization and democratic consolidation signifies the self-governing structure following the collapse of a non-democratic regime. Democracy and democratization can be instituted in implausible settings, because usually it tends to survive. There are many factors that are tangled in democratization in a unique manner. Democratization is not about a particular segment of the state as this process inculcates in all the segments. The methodology of this research grounded on desk review which using the qualitative method and primarily contemplates the theoretical basis of democratization. The research finds out that the developing countries do not have consolidated democracy because their practices are incomparable to the standards and factors of democratization. To strengthen the democracy, strong institutional building, civic education, economic advancement, free and fair elections, and inclusive politics are deemed necessary to be inculcated in the system. This research recommends to struggling democracies to consider ten factors of Michael J. Sodaro for democratization.